Islamic Leadership to Improve the Quality of Islamic Education Institutions at MTs YP. Ummul Quraa Tembung, Percut Sei Tuan District, Deli Serdang Regency - Salwa Nabila Damanik; Makmur Syukri (Manajia: Journal of Education and Management, 2024)
The aim of this research is to explain Islamic Leadership to Improve the Quality of Islamic Education Institutions at Mts Yp. Ummul Quraa, the method used in this research is a descriptive research method using qualitative. Data was obtained from interviews, observation and documentation. The findings from this research indicate that improving the quality of Islamic educational institutions, for example, will be greatly influenced by the leadership produced by the people tasked with managing Islamic educational institutions. Islamic leadership includes many features that can be used by leaders of Islamic educational institutions to carry out leadership tasks. Islamic leadership is a concept of balancing worldly leadership with the concept of the afterlife; achieving the organization's ultimate goals is more than just a temporary goal; This requires a strong commitment to Islamic principles, and the task of leadership is not just a humanitarian task that is not accountable outside the members, but must also be accountable before God Almighty.